2022
DOI: 10.14202/vetworld.2022.83-90
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic resistance status of goat gastrointestinal nematodes in Sing Buri Province, Thailand

Abstract: Background and Aim: Promotions of goat farming by both public and private sectors encouraged considerable goat raising in central Thailand. Gastrointestinal nematodes (GIN) infection is a major health and economic problem; however, evidence of resistance to broad-spectrum anthelmintics is frequently reported. Investigation of anthelmintic resistance (AR) status and identification of factors related to the development of AR is important components for sustainable GIN control. However, no information is availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“… 28 Nevertheless, our finding is not consistent with other reports of a 100% reduction in egg count in goats in different parts of Ethiopia 32 , 35 and elsewhere in Europe. 36 On the other hand, Ratanapob et al, 11 Gelot et al, 31 and Eysker et al 37 reported the presence of ivermectin resistance against the nematode population in goats in Thailand, India, and the Netherlands. The suspected resistance of ivermectin might be attributed to the frequent use of this drug by professionals when controlling gastrointestinal helminths in ruminants because of their broad spectrum and endectocide activity; this encourages excessive use and may lead to lower efficacy over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 28 Nevertheless, our finding is not consistent with other reports of a 100% reduction in egg count in goats in different parts of Ethiopia 32 , 35 and elsewhere in Europe. 36 On the other hand, Ratanapob et al, 11 Gelot et al, 31 and Eysker et al 37 reported the presence of ivermectin resistance against the nematode population in goats in Thailand, India, and the Netherlands. The suspected resistance of ivermectin might be attributed to the frequent use of this drug by professionals when controlling gastrointestinal helminths in ruminants because of their broad spectrum and endectocide activity; this encourages excessive use and may lead to lower efficacy over time.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 12 , 41 It also showed that farmers in the study area perform several practices that may be responsible for promoting the development of AR, which is in line with previous studies conducted in different parts of the world. 6 , 11 , 32 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastrointestinal nematode (GIN) infections are one of the major problems facing livestock producers worldwide, and there is growing concern about the increase in drug resistance to all major classes of anthelmintics ( 1 , 2 ). Once controlled predominantly by anthelmintics, overuse and abuse have led to resistance against most major classes of drugs ( 3 7 ). Meat and milk producers have resorted to less than adequate management-based control strategies, especially for those parasites that are the most pathogenic, i.e., Haemonchus spp., Ostertagia ostertagi, and Teladorsagia circumcincta .…”
Section: Introductionmentioning
confidence: 99%